Chemistry and Applications of Benzimidazole and its Derivatives - Marinescu, Maria (IntechOpen, 2019)
Finding new strategies for synthesizing benzimidazole derivatives and functionalizing the benzimidazole core has proved to be important due to the compound's various applications in medicine, chemistry, and other areas. The multitude of benzimidazole derivatives marketed as drugs has led to intensive research in the field for the discovery of new biologically active structures. The general applications of benzimidazole derivatives in materials chemistry, electronics, technology, dyes, pigments, and agriculture open up new research horizons. This book guides the rational design of benzimidazole derivatives synthesis with certain applications. Chapters cover such topics as therapeutic use of benzimidazole in conditions like diabetes, viruses, and parasitic diseases; X-ray crystal structure of selected benzimidazole derivatives; benzimidazole compounds for cancer therapy; and others.